Insights into the effects of apelin-13 on renal function and NHE3 activity following ischemia/reperfusion-induced acute kidney injury - Lopes-Gonçalves, Guilherme; Costa-Pessoa, Juliana Martins; de Ponte, Mariana Charleaux; Braz, Heitor Macedo; Oliveira-Souza, Maria (Frontiers in Physiology, 2025)
IntroductionAcute kidney injury (AKI) is a clinical syndrome characterized by rapid decline in renal function with varying severity. In this context, tubular function is impaired in ischemia-induced AKI. Although there are no effective therapies for AKI, many compounds have been reported to reduce kidney injury, such as apelin-13. Considering the relevance of proximal tubular cells in maintaining fluid and electrolyte homeostasis, the effects of apelin-13 on tubular injury or sodium proximal transport remain unclear. Thus, the present study aims to evaluate the effects of exogenous administration of apelin-13 in the renal ischemia/reperfusion (I/R) model, with particular focus on renal function, injury markers, and tubular proliferation.MethodsMale C57BL/6 mice were initially treated with a vehicle or high dose of apelin-13 (200 μg/kg/day) and subjected to kidney bilateral ischemia procedure for 30 min or a sham surgery. The mice were euthanized by exsanguination 2 d after the ischemic procedure. Then, the renal function was assessed through the plasma urea level and creatinine clearance. Tubular injury was evaluated by hematoxylin and eosin staining. Kidney injury molecule 1 (KIM-1), neutrophil gelatinase-associated lipocalin (NGAL), megalin, Ki67, and phospho ERK 1/2 (Thr202/Tyr204) were evaluated through immunohistochemical or immunoblotting experiments. Moreover, the murine proximal tubular cells (TKPTS) were treated with apelin-13 (100 nM) to evaluate the activity of the Na+/H+ exchanger isoform 3 (NHE3) via intracellular pH measurements.ResultsInitial administration of apelin-13 did not improve tubular injury, creatinine clearance, or plasma urea level after renal I/R. Moreover, KIM-1 and NGAL markers were markedly increased after renal I/R and were not reduced in the apelin-13 + I/R group. Furthermore, megalin downregulation by renal I/R was not prevented by apelin-13. Interestingly, apelin-13 worsened the renal responses to tubular proliferation after renal I/R as Ki67 and phosphorylation of ERK/1/2 (Thr202/Tyr204) were sharply reduced in the apelin-13 + I/R group. In vitro experiments also demonstrated that apelin-13 inhibited NHE3 activity in murine proximal tubular cells.ConclusionThe overall findings suggest that apelin-13 suppresses tubular proliferation and potentially impairs the adaptive response to renal I/R injury, thereby highlighting its relevance in ischemia-induced AKI.